Syntheses and bio-activities of the L-enantiomers of two potent transition state analogue inhibitors of purine nucleoside phosphorylases. - Clinch, K; Evans, G; Fleet, G; Furneaux, R; Johnson, S; Lenz, D; Mee, S; Rands, P; Schramm, V; Taylor Ringia, E; Tyler, P (2006)
(1R)-1-(9-Deazahypoxanthin-9-yl)-1,4-dideoxy-1,4-imino-L-ribitol [(+)-5] and (3S,4S)-1-[(9-deazahypoxanthin-9-yl)methyl]-4-(hydroxymethyl)pyrrolidin-3-ol [(-)-6] are the L-enantiomers of immucillin-H (D-ImmH) and DADMe-immucillin-H (D-DADMe-ImmH), respectively, these D-isomers being high affinity transition state analogue inhibitors of purine nucleoside phosphorylases (PNPases) developed as potential pharmaceuticals against diseases involving irregular activation of T-cells. The C-nucleoside hydrochloride D-ImmH [(-)-5) x HCl], now "Fodosine" is in phase II clinical trials as an anti-T-cell leukaemia agent, while D-DADMe-ImmH is a second generation inhibitor with extreme binding to the target enzyme and has entered the clinic for phase I testing as an anti-psoriasis drug. Since the enantiomers of some pharmaceuticals have revealed surprising biological activities, the L-nucleoside analogues (+)-5 x HCl and (-)-6, respectively, of D-ImmH and D-DADMe-ImmH, were prepared and their PNPase binding properties were studied. For the synthesis of compound (-)-6 suitable enzyme-based routes to the enantiomerically pure starting material (3S,4S)-4-(hydroxymethyl)pyrrolidin-3-ol [(-)-6] and its enantiomer were developed. The L-enantiomers (+)-5 x HCl and (-)-6 bind to the PNPases approximately 5- to 600-times less well than do the D-compounds, but nevertheless remain powerful inhibitors with nanomolar dissociation constants.